(untitled) (MMIT Proceedings, 2025)
For the provision of services to subscribers of optical access networks in the GeoUtr program, JSC “Uzbektelecom”’s optical fiber networks play a key role in the transmission of large amounts of data such as video, audio, and high-speed Internet. They also provide opportunities for further expansion and modernization of the network infrastructure